Dynamic modeling and rolling data analysis of the tandem hot rolling process. (April 2017) - Fang-chen, Yin; Dian-hua, Zhang; Yu-cheng, Zhang
Hot rolling is an essential industrial process in the production of sheet steel, a widely used product in manufacturing and construction. The hot strip mill is a complex unit including many processes and control loops and its modeling is a challenging task owing to the variety of phenomena that occur within the mill. Model validation is also challenging owing to a scarcity of measurements. In this study, a computer simulative emulation that can analyze the dynamic behaviors of the tandem hot rolling process with original non-linear rolling models has been developed and validated against a linear model and measured data. Moreover, the influence coefficients of rolling process parameters were calculated by analyzing the rolling data.